First report of a field outbreak of a leaf miner, stomphastis thraustica meyrick (lepidoptera: gracillariidae on bioenergy crop jatropha curcas L.(euphorbiaceae)in Malaysia. - Sajap, Ahmad Said (2010)
An outbreak of a leaf miner, stomphastis thraustica meyrick (lepidoptera; gracillariidae) on jatropha curcas L.(euphorbiaceac) was reported for the first time in Malaysia. This leaf miner couses severve bloth mines on leaves of young seedlings in a nursery. Even though most of the seedlings survived from the first infestation but they might not survive in repeated infestations. Such outbreaks could pose a serious economic implicaton on productivity of the crop. Thus, much more research is required into the growing and management of J.curcas, including its pest management, to realize the full potential of the plant.